Akanthomyces araneogenum, a new Isaria-like araneogenous species - Chen, Wan-Hao; Liu, Chang; Han, Yan-Feng; Liang, Jian-Dong; Liang, Zong-Qi (Phytotaxa, 2018)
During a survey of araneogenous fungi from Guizhou Province, China, a new species, Akanthomyces araneogenum, was isolated from a spider, Araneus sp. It differs from other Akanthomyces species by its spider host, Isaria-like conidiogenous structure, and mostly globose and smaller conidia (1.6–2.2 μm). Multi-locus (ITS, LSU, RPB1, RPB2 and TEF) phylogenetic analysis confirmed that A. araneogenum is distinct from other species. The new species is formally described and illustrated, and compared with similar species.